Altered Mitochondrial Protein Homeostasis and Proteinopathies - Jishi, Aya; Qi, Xin (Frontiers in Molecular Neuroscience, 2022)
Increasing evidence implicates mitochondrial dysfunction as key in the development and progression of various forms of neurodegeneration. The multitude of functions carried out by mitochondria necessitates a tight regulation of protein import, dynamics, and turnover; this regulation is achieved via several, often overlapping pathways that function at different levels. The development of several major neurodegenerative diseases is associated with dysregulation of these pathways, and growing evidence suggests direct interactions between some pathogenic proteins and mitochondria. When these pathways are compromised, so is mitochondrial function, and the resulting deficits in bioenergetics, trafficking, and mitophagy can exacerbate pathogenic processes. In this review, we provide an overview of the regulatory mechanisms employed by mitochondria to maintain protein homeostasis and discuss the failure of these mechanisms in the context of several major proteinopathies.